A Pseudorandom Binary Generator Based on Chaotic Linear Feedback Shift Register - Falih, Saad Muhi (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This paper presents a simple method for the design of Chaotic Linear Feedback Shift Register (CLFSR) system. The proposed method is based on a combination of two known systems. The first is called Linear Feedback Shift Register (LFSR) system, and the other is called Chaotic Map system. The main principle of the proposed system is that, the output of the LFSR is modified by exclusive-or (XOR) it with the stream bit that is generated by using the chaotic map system to eliminate the linearity and the repeating in the output of the LFSR system. The proposed system is built under Matlab environment and the quality of sequence generation tested by using standard tests which shows that the proposed system is a good random number generator that overcome the linearity and repeating disadvantages.